The Absolute Standardization Methods of 32P for Calibrate Nuclear Medicine Instruments in Indonesia - G. Wurdiyanto; H. Candra; H Holnisar; V. Pungkun (PPIKSN-BATAN, 2019)
The absolute standardization of 32P radioactive sources employedto calibrate nuclear medicine instruments has been conductedat PTKMR-BATAN. We deemed this activity to be necessarysince 32P used in the nuclear medicine fields has a short half-life, and in order to obtain a result of quality measurement, it requires a special treatment. Moreover, in Indonesia, the use of nuclear medicine techniques has developed rapidly. We prepared all the radioactive sources witha gravimetric method by using a KERN ABT 220-5DMsemi-micro type scale, traceable to the International Unit System. We conductedthe 32P standardization by employing a 4πβ(PS)-γ coincidence method with 60Co as a tracer;meanwhile, we conducted the impurity measurementby employing a beta spectrometer system. The result of 32P absolute measurement was 380.05 Bq/mg with a 0.68-percentrange uncertainty, witha k=2coverage factor. This value was used to calibrate a “Capintec CRC-7BT”dose calibrator that was a secondary standard instrument in PTKMR-BATAN. The results showed us that the calibration factor of the “Capintec CRC-7BT” dose calibrator was 1.12 witha 4.7-percent uncertainty.